New topical treatment of vulvodynia based on the pathogenetic role of cross talk between nociceptors, immunocompetent cells, and epithelial cells - Keppel Hesselink JM (Journal of Pain Research, 2016)
J M Keppel Hesselink,1 D J Kopsky,2 N Sajben3 1Institute for Neuropathic Pain, Bosch en Duin, 2Institute for Neuropathic Pain, Amsterdam, The Netherlands; 3Scripps Memorial Hospital La Jolla, La Jolla, CA, USA Abstract: Topical treatments of localized neuropathic pain syndromes in general are mostly neglected, mainly due to the fact that most pain physicians expect that a topical formulation needs to result in a transdermal delivery of the active compounds. On the basis of the practical experience, this study brings forth a new, somewhat neglected element of the vulvodynia pathogenesis: the cross talk between the nerve endings of nociceptors, the adjacent immunocompetent cells, and vaginal epithelial cells. Insight into this cross talk during a pathogenic condition supports the treatment of vulvodynia with topical (compounded) creams. Vulvodynia was successfully treated with an analgesic cream consisting of baclofen 5% together with the autacoid palmitoylethanolamide 1%, an endogenous anti-inflammatory compound. In this review, data is presented to substantiate the rationale behind developing and prescribing topical products for localized pain states such as vulvodynia. Most chronic inflammatory disorders are based on a network pathogenesis, and monotherapeutic inroads into the treatment of such disorders are obsolete. Keywords: vulva, cream, autacoid, mast cell, pain, analgesia, pathogenesis, baclofen, palmitoylethanolamide